IGH/BCL2 Status Better Predicts Clinico-Pathological Behavior in Primary Splenic Follicular Lymphoma than Histological Grade and Other Molecular Markers - Cherian Verghese; Weihong Li; Nanuli Gvazava; Emmanouil Alimpertis; Navkirat Kahlon; Hongliu Sun; Robert Booth (SAGE Publishing, 2022)
Splenic lymphoma may be primary or secondary. Primary splenic lymphoma's are rare and usually of follicular cell origin representing <1% of Non-Hodgkin's Lymphoma's. Most are secondary with 35% representing Marginal Cell sub-type with the rest being Diffuse Large B-Cell Lymphoma's. Unlike the uniformly aggressive clinical course of Diffuse Large B-Cell Lymphoma's, biological behavior of Primary Splenic CD10-Positive Small B-Cell Lymphoma/Follicular Lymphoma remains less well defined. We present here a solitary splenic mass confirmed as Primary Splenic CD10-Positive Small B-Cell Lymphoma/Follicular Lymphoma after a diagnostic splenectomy. Biopsy revealed monomorphic small lymphoid cells with low grade mitotic activity. Flow cytometry showed a lambda restricted population of B-Cells displaying dim CD19 and CD10. The cells were negative for CD5, CD11c, and CD103. FISH was negative for IGH/BCL2 fusion unlike nodal Follicular Lymphoma's which are usually positive for this translocation. Evidence from this case and a review of literature support the finding that Primary Splenic CD10-Positive Small B-Cell Lymphoma/Follicular Lymphoma is less likely to have the classic IGH-BCL2 fusion and the associated chromosomal 14;18 translocation. This profile is associated with less aggressive clinical behavior even when histopathology represents a high-grade pattern. In such cases splenectomy alone is adequate for localized disease when negative for IGH/BCL2 fusion regardless of histological grade.